Avaliação in vitro do efeito de três métodos de soldagem no desajuste marginal de estruturas em cobalto-cromo utilizados em próteses sobre implantes - Barbi, Francisco Carlos Lazzaro (2010)
Statement of problem: The final influence of different methods for joining prosthesis wer implants on the levei of marginal misfit is still not well known. Purpose of study: To assess the effects of three different methods of joining prosthetic tructures on the marginal misfit of test specimens cast in a Cobalt-Chromium alloy 'Iaced over intermediates used in prosthesis over impiants. Material and methods: A specially designed device was used for casting, joining and easuring the marginal misfit. Forty-five specimens were fabricated and randomly ivided into three groups with 15 specimens each: Group 1 - brazing; Group II - laser; nd Group III - TIG. The marginal misfit was measured using the one-screw test and electron scanning microscopy in three different positions: D (Distal), C (Central) e M (Mesial) on the vestibular face of both abutments A (reference) and B (test). Welsh's ANOVA was applied on the data at a level of significance of 95% (p <0,05). Results: statistically significant differences were found on abutment A between brizing and laser (p = 0,0134) in M, and between brazing and TIG (0,0366) in C. On the abutment B significant differences were found between brazing and laser (p < 0,0001) and laser and TIG (p < 0,0001) in M; brazing and TIG (p = 0,0069) in D; and between brazing and TIG (p = 0,0003) and laser and TIG (p = 0,0079) in C. Conclusions: The method for joining prosthetic structures had an influence on the level marginal misfit. Structures joined by TIG method produced the best average results in comparison to brazing and laser methods.